Today's market prices - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Today´s market prices, Agriculture 21 (FAO) The biggest problem facing agricultural market information services is getting their information to farmers. Local FM radio stations may be part of the solution...